Morphological and functional outcome of scleral buckling surgery compared to primary vitrectomy in patients with retinal detachment - Stamenković, Miroslav; Stefanović, Ivan; Senćanić, Ivan; Jakšić, Vesna; Mavija, Milka; Babović, Siniša (Vojnosanitetski pregled, 2014)
Background/Aim. Among the proposed operative techniques for retinal detachment (RD) the most commonly applied are classical method with scleral buckling and pars plana vitrectomy (PPV). The aim of this paper was to determine which surgical intervention of these two leads to better morphological results in terms of the applied retina and better functional outcomes in terms of visual acuity (VA) of the operated eye in patients with RD. Methods. A retrospective study on the comparative section of the effects of scleral buckling surgery and PPV in uncomplicated rhegmatogenous RD was performed. In a 2-year period 97 patients, i.e. 98 eyes with RD were operated on (68 eyes with scleral buckling surgery vs 30 by PPV). Results. In the group with classically operated detachment, the retina was applied in 52 (76.5%) cases vs 30 (100%) patients in PPV group (p
Keywords: retinal detachment; scleral buckling; vitrectomy; visual acuty; treatment outcome